LUT-Based Focal Beamforming System Using 2-D Adaptive Sequential Searching Algorithm for Microwave Power Transfer - Bae, Jongseok; Yi, Sang-Hwa; Koo, Hyungmo; Oh, Sungjae; Oh, Hansik; Choi, Woojin; Shin, Jaekyung; Song, Chan Mi; Hwang, Keum Cheol; Lee, Kang-Yoon; Yang, Youngoo (IEEE access, 2020)
This paper presents a look-up table (LUT)-based focal beamforming system that can effectively transmit RF power up to mid-range distances (≤ 3 m) including when the Rx is in the near-field zones. The Tx elements control and radiate signals for the Rx even at the near-field zone ensuring the received signals are in-phase. Since the proposed system uses a LUT for storing the phase sets of the signals for the Tx elements, it requires only very simple hardware and a very simple adaptive control algorithm compared to conventional retroreflective method. In order to track the moving Rx, a 2-D adaptive sequential searching algorithm is proposed. The system can find the optimum phase set by sequentially searching the phase sets for a pre-determined 2-D area. The LUT of the phase sets are generated using geometric analysis over the entire 2-D area where the Rx could be located. To verify the proposed method, a 5.2 GHz mid-range (≤ 3 m) MPT system composed of a 4× 8 Tx array and a 2× 3 Rx array was designed and implemented. Using the proposed 2-D adaptive sequential searching algorithm, the optimum phase set for focal beamforming can be quickly found for a given position of the Rx. In our experiments, the results showed an RF power level of 177.8 mW was received at the Rx with a distance of 1 m with a total radiated RF power of 16W. Since the measured received power levels for various Rx positions agree well with the simulation results, the proposed system was proved to be an excellent candidate for the practical application.